PENDEKATAN LITERASI DIGITAL DALAM PEMBELAJARAN MENULIS AKADEMIK: PEMANFAATAN DAN TINGKAT LITERASI MAHASISWA - Abdul Haliq; Shafariana Shafariana (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the use of a digital literacy approach in academic writing learning and the level of student digital literacy in academic writing. The research method used is descriptive qualitative. The research subjects were lecturers and students enrolled in the scientific writing course at the Department of Indonesian Language and Literature. Data collection techniques used questionnaires, interviews, and documentation. The research instrument was a digital literacy questionnaire developed based on Bawden's (2008) digital literacy theory. The results showed that academic writing learning utilizes four aspects of digital literacy: digital competence, knowledge of information background, main skills, and attitudes and perspectives. Furthermore, the level of student digital literacy is generally in the very high and high categories. This indicates that students have very good digital literacy skills for use in academic essay writing learning using various technological devices and applications, both for learning and for writing development more specifically.